Consumer Spending and Consumer Confidence in South Africa: Cointegration Analysis - Khumalo, John (Journal of Economics and Behavioral Studies, 2014)
The study uses the time series data covering the period 1980Q1 to 2012Q3 to test the existence of any possible long run relationship between consumer spending and consumer confidence in South Africa. The analysis is done using the Vector Auto-Regressive (VAR) model, with the unit root and the direction of causation also tested before any inference can be concluded on this relationship. The unit root tests using the DF-GLS as well as the Ng-Peron show that consumer spending, consumer confidence and economic growth are integrated of order zero I(0). Causality results on the other hand reveal that causation runs from consumer confidence to consumer spending and from economic growth to consumer spending in South Africa. The non-existence of unit root compels the establishment of the long-run relationship that leads us to performing VECM to establish short-run and long-run dynamics. Our results indicate that the positive effect of consumer confidence cannot be refuted in South Africa and that it exerts a significant and positive impact on consumer spending, hence aggregate spending.